Lake Mead Developed Area Surveys: The LAME 86A Archeological Investigations and Related Projects, Lake Mead National Recreation Area, Nevada and Arizona - Ervin, Richard G. (the Digital Archaeological Record)
In early 1986, archeologists from the Western Archeological and Conservation Center (WACC), National Park Service (NPS), surveyed developed areas and other high-use areas within Lake Mead National Recreation Area (NRA). The 1986 Archeological Survey of Developed Areas was designated project LAME 86A. This report describes the results of the LAME 86A project and two earlier developed areas surveys, and so provides a complete record of such surveys at Lake Mead. One of the previous surveys was the LAME 80A project, a survey of the Willow Beach developed area (Simpson 1980). Eight prehistoric sites and one historic period mine were recorded. The second was the LAME 80F project, a survey of four developed areas: Boulder Beach, Echo Bay, Temple Bar and Cottonwood Cove (Ellis and Bergin 1981). Ten prehistoric sites (including four rockshelters, three lithic reduction sites and three groups of rock features) and six historic sites (including two trash dumps and four sites that are part of the Sullivan Turquoise Mine) were recorded. The LAME 86A project resulted in the discovery of 12 prehistoric lithic reduction sites and 88 artifact scatters or isolated features; 3 historic period sites and 23 features or trash scatters were also found. The developed area surveys provide NPS managers with a record of cultural resources in areas most likely to undergo development. This information makes project-specific archeological surveys unnecessary in developed areas. During planning for future development projects in these areas, only a records check will be needed to determine whether archeological clearance can be issued. The projects revealed several different site types within the areas surveyed. Mines are the most common type of historical site, followed by trash scatters. Two tent encampments and a mortared stone structure were found at Pearce Ferry, and a trash dump associated with the Katherine Mine was recorded at Katherine Landing. Prehistoric resources can be classed within three categories. Lithic reduction sites are most numerous, being found wherever natural chert deposits occur. The largest sites are found in the central part of Lake Mead NRA, in sedimentary formations that outcrop north, east and west of the Black Mountains. Lithic reduction sites usually lack culturally or temporally diagnostic artifacts, and their potential significance is thus low. Rock feature sites are also common. These include rock circles, rock rings and cleared areas. These features have traditionally been interpreted as the remains of shelters, an explanation that has been questioned by some archeologists. Blair (1984) has proposed that rock circles may actually represent caches or water retention features. Raab (1972) suggested that rock rings served as basket supports during the cactus fruit harvest. Goodyear (1975) later showed the distribution of rock rings correlates with the range of saguaro. No evidence was found during the LAME 86A project that cleared areas are cultural features, and it is suspected they are of natural origin. Rock feature sites of all kinds normally lack temporally or culturally diagnostic artifacts, making it impossible to relate them to the cultural sequence. In the absence of cultural or temporal information, their potential significance is low. The third class of sites is rockshelters. Four were found at Boulder Beach around granitic outcrops. Artifact densities are these sites are low, but the presence of midden soils and functionally or temporally diagnostic artifacts gives a high potential significance to these sites.